If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3y + -1)(2y) = 4 Reorder the terms: 3(-1 + 3y)(2y) = 4 Remove parenthesis around (2y) 3(-1 + 3y) * 2y = 4 Reorder the terms for easier multiplication: 3 * 2y(-1 + 3y) = 4 Multiply 3 * 2 6y(-1 + 3y) = 4 (-1 * 6y + 3y * 6y) = 4 (-6y + 18y2) = 4 Solving -6y + 18y2 = 4 Solving for variable 'y'. Reorder the terms: -4 + -6y + 18y2 = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + -6y + 18y2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + -3y + 9y2) = 0 Factor a trinomial. 2((-1 + -3y)(2 + -3y)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + -3y)' equal to zero and attempt to solve: Simplifying -1 + -3y = 0 Solving -1 + -3y = 0 Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3y = 0 + 1 -3y = 0 + 1 Combine like terms: 0 + 1 = 1 -3y = 1 Divide each side by '-3'. y = -0.3333333333 Simplifying y = -0.3333333333Subproblem 2
Set the factor '(2 + -3y)' equal to zero and attempt to solve: Simplifying 2 + -3y = 0 Solving 2 + -3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3y = 0 + -2 -3y = 0 + -2 Combine like terms: 0 + -2 = -2 -3y = -2 Divide each side by '-3'. y = 0.6666666667 Simplifying y = 0.6666666667Solution
y = {-0.3333333333, 0.6666666667}
| 3x-(4x-4)= | | 4x+3(x-6)=4(x-3) | | 15s^2-34s+15= | | 1/4w-5=-3 | | 123+k=649 | | 14x+19x-8+1=-2x+1-8 | | 3-2i=-5 | | -y^2=6y+9 | | 5x-3x+12=x+8 | | x-54=2 | | (3x+1)(p-5)=0 | | x-54=2x | | 6-2(3x)-x= | | 6-2(3x-4)= | | 3(2+3x)=8(x-5) | | 18-5y+12+2y= | | a+10=43 | | 1/2z+7=10 | | 43-a=10 | | 6-2(3x-4)-x= | | .33x-1=.75x-6 | | 10(y+z)=2(3y+5) | | 3x-3=3x-5 | | ln(13*lnx)=-4 | | -2-3(4-x)+5x=6 | | 3x+2(5x+11)=9 | | 25=7m-3 | | (6x+1)(6x-9)= | | 10v^2+29v-21=0 | | 3m(4n+2-m)= | | 4y+8x-6=0 | | 3x-200=5000 |